Vector Graphics: From PostScript and Flash to SVG - Probets, Steve; Mong, Julius; Evans, David; Brailsford, David F. (ACM Press, 2001)
The XML-based specification for Scalable Vector Graphics (SVG), sponsored by the World Wide Web consortium, allows for compact and descriptive vector graphics for the Web.